Lectotypification of three names in Carex subg. Vigneastra (Cyperaceae) from Asia - Bi, Hai-Yan; Zhang, Shu-Ren (Phytotaxa, 2017)
Three names of Carex Linnaeus (1753: 972) (Cyperaceae), namely Carex composita Boott (1858: 3), Carex myosurus Nees in Wight (1834: 122), Carex stramentitia Boott ex Boeckeler (1876: 351) are lectotypified as a part of the revision of Carex subg. Vigneastra (Tuckerman 1843: 10) Kükenthal (1899: 516) for the Flora of Pan-Himalaya.